Influence of the director anchoring energy on a light induces Freedericksz transition threshold in the bounded light beams - Berezovskaya, A.A.; Yezhov, S.N.; Ledney, M.F.; Pinkevych, I.P. (Functional Materials, 2007)
Director transition threshold values are numerically calculated for the hemeotropic nematic cell under the field of spatially bounded light beams in depending on the director anchoring energy with the cell surface. Analytical expressions for the threshols in the wide and narrow light beams are obtained for the cases of strong and weak director anchoring. It is shown that influence of the anchoring energy finite values increase with decreasing of the beam cross-section. It is appear to be the most strong at the weak director anchoring.